A trajetória política de Cristina Tavares: a redemocratização e os direitos das mulheres na Constituição Cidadã (1978 – 1988). - Silva, Edvaldo dos Santos (2021)
This study aims to understand the political role of Congresswoman Cristina Tavares, the first woman elected by Pernambuco to the Chamber of Deputies, in the process of redemocratization in Brazil and in the struggle for women's rights in the Constitution of 1987-1988, briefly revisiting the its participation in the main political events that preceded the convening of the National Constituent Assembly. The pioneering spirit of the congressman from Pernambuco in the face of the historical invisibility of women in the national political scene aroused interest in learning about her action, as a federal deputy, in the defense of women's rights. The investigation proposed to think about the political trajectory of this plural woman, under construction, inserted in a complex network of power. The instruments used in the analysis consist of documentary sources and collection of oral testimonies, research in libraries and public archives, in addition to a dialogue with the historiography of the period. This master's conclusion work built an e-book about the trajectory of Cristina Tavares' political trajectory as a product of the historical research developed.